Service Quality and Customer Satisfaction on WOM a Private Hospital in Indonesia - Tantri Yanuar Rahmat Syah; Cahyo Kusumo Wijoyo (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
This research examines the effect of service quality and customer satisfaction on word of mouth. We carried out a survey of our sample, which consisted of 303 respondents. This study provides empirical evidence that service quality has a significant positive effect on customer satisfaction, service quality also has a significant positive effect on word of mouth and customer satisfaction has a significant positive effect on word of mouth.